Gingivitis efficacy of a 0.454% w/w stannous fluoride dentifrice: a 24-week randomized controlled trial - C. R. Parkinson; K. R. Milleman; J. L. Milleman (BMC, 2020)
Abstract Background Plaque-induced gingivitis can be prevented and treated with regular effective oral hygiene, principally via mechanical cleaning with regular toothbrushing. To complement the mechanical plaque removal, antimicrobial ingredients can be incorporated into dentifrices to inhibit the growth of plaque. This study aimed to evaluate and compare gingivitis and the proportion of subjects moving between gingivitis severity (< 10, > 10 < 30, > 30% bleeding sites), and plaque reduction, following twice daily use of an experimental non-aqueous 0.454% weight/weight (w/w) stannous fluoride (SnF2) dentifrice, compared to a negative control dentifrice over 12 and 24 weeks. Method This was a single-center, examiner-blinded, randomized, stratified, two-treatment arm, parallel group, 24-week clinical study in healthy adult volunteers with moderate gingivitis. At baseline, after abstaining from toothbrushing overnight, subjects underwent MGI (modified gingival index), BI (bleeding index) and PI (plaque index) assessments. Eligible subjects, who met the inclusion/exclusion criteria, were stratified based on gender and baseline mean MGI score (Low ≤2.00 /High > 2.00) and randomized to treatment. Following randomization, subjects underwent a thorough dental prophylaxis and flossing. After 12 and 24 weeks of twice daily brushing with their allocated treatment, subjects returned to the site (with overnight plaque, having abstained from oral hygiene procedures for 8 h prior to visit) for MGI, BI and PI assessments. Treatment effect was evaluated by comparing the MGI, BI and PI scores. Results One hundred and twenty-nine subjects were screened; 98 subjects were randomized and 90 subjects completed the study. Statistically significant differences between treatments, in favour of the 0.454% stannous fluoride dentifrice were observed, compared to the negative control dentifrice, for all outcome measures (MGI, BI, bleeding sites and PI at weeks 12 and 24 p < 0.0001). At 24 weeks, 71% of subjects in the 0.453% SnF2 treatment group demonstrated < 10% of bleeding sites. Conclusion A dentifrice containing 0.454% w/w SnF2 was shown to be superior to a standard dentifrice in controlling gingivitis and supra-gingival plaque, over a 24-week period. Over two thirds of subjects in the 0.454% SnF2 treatment group demonstrated a level of bleeding sites potentially representative of "clinical periodontal health" (< 10%) following a dental prophylaxis and 24 weeks of product use. Trial registration This study was retrospectively registered at ClinicalTrials.gov, on 11th Oct. 2019 ( NCT04123665 ).